Analisis Kritis Kebijakan Kurikulum: Antara KBK, KTSP, K13 Dan Kurikulum Merdeka - Nisa, Khoirun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this research is to understand the differences, advantages, disadvantages, and impacts caused by curriculum policies and explore the four main curriculum policies, namely Competency-Based Curriculum (KBK), Education Unit Level Curriculum (KTSP), Curriculum 2013 (K13), and the Independent Curriculum. This research uses a qualitative approach with the type of library research, in order to evaluate curriculum policies based on relevant aspects such as educational goals, learning approaches, curriculum content, and evaluation methods. We also explore the historical context and ideology behind each of these curriculum policies. The results of our analysis show that each curriculum policy has different characteristics and objectives. KBK, as the first curriculum policy after the education reform, emphasizes competency development and holistic understanding of students. KTSP, despite its flexibility, faces challenges in its implementation due to a lack of national guidelines and uniformity. K13, which was adopted with the aim of improving the previous curriculum, emphasized fulfilling Graduate Competency Standards (SKL) and improving basic competencies. Meanwhile, the Independent Curriculum offers a more open approach and gives schools flexibility in designing curricula according to local needs and characteristics. In conclusion, curriculum policy in Indonesia reflects a continuous effort to improve the education system. However, each policy has advantages and disadvantages that need to be considered. In facing global challenges and preparing young people for the future, it is important to continue to critically analyze curriculum policies, improve existing weaknesses, and integrate elements that can increase educational effectiveness.